COMMUNITY PERCEPTIONS OF FREE SOCIAL INTERACTION DURING THE ENGAGEMENT PERIOD - Huda, Tsalisul; Riyanto, Ridho (Al-Mubin, 2025)
Engagement (khitbah) is an important stage preceding marriage in Muslim community traditions. However, in practice, the engagement period is often misinterpreted as a time of freedom in interactions between prospective couples. This study aims to explore the perceptions of the Maling Mati Village community regarding the phenomenon of free social interaction during the engagement period, as well as the contributing factors and impacts. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The findings indicate that most community members lack a proper understanding of the Islamic legal boundaries during khitbah, resulting in tolerance of unrestricted interaction between engaged couples, which in some cases leads to premarital pregnancy. The main factors behind this phenomenon include low religious literacy, weak roles of families and community leaders, and the influence of popular culture. This study recommends the necessity of value-based education and structured premarital guidance provided by religious and social institutions. Thus, moral values and Islamic teachings can be preserved throughout the marriage preparation process